THE EFFECTS OF ACCENT FAMILIARITY ON ARAB EFL LEARNERS’ PERCEPTIVE INTELLIGIBILITY - Nazari, Ahmad; Younus, Majid Rasim (LLT Journal: A Journal on Language and Language Teaching, 2021)
In accord with the current status of English as an International Language, the aim of this article is to develop a methodological framework to investigate the effects, if any, of accent familiarity on perceptive intelligibility in an Arab EFL context. To this end, a perception intelligibility test was developed to measure the intelligibility of Arab EFL learners and to determine the extent to which intelligibility varied in relation to accent familiarity. A listening text in English from the Speech Accent Archives produced by three speakers of different first language backgrounds constituted the material stimulus for the perceptive intelligibility test. In this respect, three accent familiarity levels were determined when measuring the perceptive intelligibility of Arab EFL learners. These accent familiarity levels included matched, mismatched and unfamiliar. The listeners were 60 randomly selected Arab EFL undergraduate students. An analytic five-point rating scale was also developed to measure the extent to which Arab EFL learners understood the English speech produced by speakers from the three different first language backgrounds. The results, in general, showed that Arab EFL learners understood with little effort most of the English utterances produced by the three English language speakers from different language backgrounds. However, the learners faced more effort and misunderstanding regarding the third speaker who represented an unfamiliar accent. The article concludes with a description of the research implications and applications that derive from the findings of the study.